Analysis of multicrystal pump–probe data sets. II. Scaling of ratio data sets. Issue 2 (16th February 2016) - Fournier, Bertrand; Sokolow, Jesse; Coppens, Philip
Abstract : The crucial need for scaling of multicrystal data sets and for the correction of the light‐induced response anisotropy inside a data set in time‐resolved pump–probe crystallography is discussed. An application of methods developed is presented. Abstract : Two methods for scaling of multicrystal data collected in time‐resolved photocrystallography experiments are discussed. The WLS method is based on a weighted least‐squares refinement of laser‐ON/laser‐OFF intensity ratios. The other, previously applied, is based on the average absolute system response to light exposure. A more advanced application of these methods for scaling within a data set, necessary because of frequent anisotropy of light absorption in crystalline samples, is proposed. The methods are applied to recently collected synchrotron data on the tetra‐nuclear compound Ag2 Cu2 L 4 with L = 2‐diphenylphosphino‐3‐methylindole. A statistical analysis of the weighted least‐squares refinement residual terms is performed to test the importance of the scaling procedure.